AMETHYST: automatic alarm assessment: operational experience - Horner, M.; Leach, G.; O'Dwyer, T. (2000 34th Annual IEEE International Carnahan Conference on Security Technology, 2000)
The aim of the AMETHYST (Automatic Event Authentication Systems) project is to encourage the development of a high-performance perimeter detection system by using video assessment to enhance the Perimeter Intrusion Detection System (PIDS). AMETHYST will automatically assess the cause of all PIDS alarms and pass to an operator only those alarms that are likely to be caused by an intruder. It will therefore filter out alarms that are not likely to have a human cause.